Efek Orientasi Pasar, Inovasi Produk dan Kualitas Produk Terhadap Keunggulan Bersaing - Asniwati; Latief, Fitriani (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The purpose of this study was to examine the effect of entrepreneurial orientation, pricing strategy and location on competitive advantage. This research is included in causal associative research using a quantitative approach. The population in this study were MSMEs in Biringkanaya District, Makassar City with a total of 453 MSMEs. The sample is part of the population. The sample consists of a number of selected members. The sample of this study used purposive sampling method, so the total sample was 55 respondents. Multiple linear regression analysis techniques. The results showed that partially market orientation, product innovation and product quality have a significant effect on the competitive advantage of MSMEs in Makassar City..